2016
DOI: 10.3389/fpls.2016.00504
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the SBP-Box Family Genes under Phytophthora capsici Stress in Pepper (Capsicum annuum L.)

Abstract: SQUAMOSA promoter binding protein (SBP)-box genes encode plant-specific transcription factors that are extensively involved in many physiological and biochemical processes, including growth, development, and signal transduction. However, pepper (Capsicum annuum L.) SBP-box family genes have not been well characterized. We investigated SBP-box family genes in the pepper genome and characterized these genes across both compatible and incompatible strain of Phytophthora capsici, and also under different hormone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 57 publications
7
61
1
Order By: Relevance
“…The expression of the CABPR1 gene in pepper was higher in the virulent strain interaction versus the avirulent interaction [60]. However, in contrast to our previous studies [61], it was found that the expression of most CaSBPs was comparatively greater in the avirulent interaction than in the compatible interaction. Some other studies have revealed that the expression of oxysterol-binding protein gene ( CanOBP ) and a novel peroxidase gene ( CanPOD ) were higher in the incompatible interaction [62,63] and the defense-related genes such as b-1, 3-glucanase gene ( CABGLU ), disease-associated protein gene ( CABPR1 ), and peroxidase gene ( CAPO1 ) were expressed in a similar pattern, after the inoculation of virulent and avirulent strains of Phytophthora capsici on the roots of pepper as reported by Wang et al (2013) [62].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The expression of the CABPR1 gene in pepper was higher in the virulent strain interaction versus the avirulent interaction [60]. However, in contrast to our previous studies [61], it was found that the expression of most CaSBPs was comparatively greater in the avirulent interaction than in the compatible interaction. Some other studies have revealed that the expression of oxysterol-binding protein gene ( CanOBP ) and a novel peroxidase gene ( CanPOD ) were higher in the incompatible interaction [62,63] and the defense-related genes such as b-1, 3-glucanase gene ( CABGLU ), disease-associated protein gene ( CABPR1 ), and peroxidase gene ( CAPO1 ) were expressed in a similar pattern, after the inoculation of virulent and avirulent strains of Phytophthora capsici on the roots of pepper as reported by Wang et al (2013) [62].…”
Section: Discussioncontrasting
confidence: 76%
“…“PF00187.17” was collected from Pfam database () as described in our previous study [61,77]. To further authenticate the CaChi family members, the CaChi were aligned with DNAMAN to cross check in both CM334 (Available online: ) [40] and Zunla-1 (Available online: ) [78] databases of pepper, while the obtained sequences were from the latest versions, i.e., v1.55 and v2.0, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In tomato, silencing the LeSPL-CNR gene could inhibit fruit ripening [17]. In pepper (Capsicum annuum L), CaSBP genes tended to be involved in pathogen resistance pathway against phytophthora capsici, which caused blight and fruit rot [27]. In sorghum (Sorghum bicolor L), SbSBPs tended to be involved in the ABA signaling pathway for abiotic stress response [28].…”
Section: Introductionmentioning
confidence: 99%